2019
DOI: 10.1186/s13018-019-1478-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional technology assisted trabecular metal cup and augments positioning in revision total hip arthroplasty with complex acetabular defects

Abstract: BackgroundRevision total hip arthroplasty (THA) with large acetabular defect remains a challenge. Though trabecular metal (TM) cup and augments have been introduced in defect reconstruction with good result, the accurate positioning of implant is important to avoid complications. Therefore, we aimed to evaluate the usefulness of three-dimensional (3D) simulation and 3D model in assisting implant positioning during complex revision THA.MethodsSixteen patients (18 hips) who underwent revision THA with a Paprosky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…To fill the bone defects adequately and maximize the contact with the host bone, custom-made implants are one option to address large bone defects in revision surgery [ 27 ]. TM components could provide strong initial stability and promote a deep bony ingrowth with the design of high porosity and low modulus of elasticity [ 26 ]. Currently, some studies have been carried out to evaluate the effects of a novel treatment strategy of double-cup technique applied to manage Paprosky III acetabular defects without pelvic discontinuity, and double-TM cups reconstruction was considered a credible way for acetabular revision according to their short-term results [ 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To fill the bone defects adequately and maximize the contact with the host bone, custom-made implants are one option to address large bone defects in revision surgery [ 27 ]. TM components could provide strong initial stability and promote a deep bony ingrowth with the design of high porosity and low modulus of elasticity [ 26 ]. Currently, some studies have been carried out to evaluate the effects of a novel treatment strategy of double-cup technique applied to manage Paprosky III acetabular defects without pelvic discontinuity, and double-TM cups reconstruction was considered a credible way for acetabular revision according to their short-term results [ 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the malposition of the acetabular cup and femoral head size are common surgical factors for dislocation in revision THA [ 32 ]. With the help of preoperative 3D simulation and model, complex revision THA could be managed with moderate to high accuracy and satisfied clinical outcomes [ 26 ]. Larger femoral heads could reduce the rate of dislocation, so all patients in our study were applied with 32-mm heads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…three-dimensional (3D)] designs have demonstrated high rates of long-term survival. 17 However, there is little consensus on which technique demonstrates the highest rate of implant survival and superior patient functioning while achieving the lowest rates of complication and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, custom-made 3D printed acetabular implants were developed to achieve primary implant stability, even in cases of pelvic discontinuity situations. [8][9][10]20] Çıtak et al [8] reported that 3D-printed acetabular components had a 56% complication rate in severe acetabular defects, although it was promising in future revision THA. In contrast, Aprato et al [9] showed encouraging results of the Bespoke acetabular system for Paprosky type 3B acetabular defects and all procedures were rated positively.…”
Section: Discussionmentioning
confidence: 99%